(untitled) (Élisée - Revista de Geografia da UEG, 2021)
Abstract: With this article, our purpose is to explain the acquisition of land and the formation of rural settlements across the Southeast of Goiás State, focusing on the struggle for land, as experienced by politically engaged men and women. This research study uses a qualitative approach, encompassing a theoretical, documentation, and field investigations performed through semi-structured interviews and photographic records. For this study, we have focused our research efforts on six settlements: João de Deus (Silvânia, 1987), São Sebastião (Silvânia, 1997), Olga Benário (Ipameri, 2005), Madre Cristina (Goiandira, 2009), Buriti (Silvânia, 2009, and Maria da Conceição (Orizona, 2010). The settlements emerge as field workers’ territories since many individuals - men, women, and families - who have re-territorialised there, thus posing as a counterpoint to the capitalist agricultural practice prevailing in the Southeast of Goiás State. This re-territorialisation has been enabled by political actions, along with social movements, unions, and federations of family-based agriculture workers, based on the material and subjective production of life in time, and in their daily lives. Keywords: Re-territorialisation. Territory. Rural settlements. Southeast of Goiás State.